Using mobile devices to enhance inquiry-based learning processes. (October 2020) - Becker, Sebastian; Klein, Pascal; Gößling, Alexander; Kuhn, Jochen
Abstract: Technological advances offer the possibility of using mobile devices to enrich learning environments with multimedia content. Although physical experiments play a key role in science learning, little is known about integrating multimedia learning in physical experimental processes, especially in realistic classroom settings. In our approach, students use tablets to investigate motion with an application providing multiple representations of the measurement data. We present the results of a cluster-randomized controlled study with high school students (average age = 15.6, N  = 286) conducted between 2017 and 2018 in 11 secondary schools in Germany. Conceptual understanding of physics, cognitive load, and assessment of teacher behavior were surveyed. Multilevel regression analysis revealed that this approach leads to a significant reduction of extraneous cognitive load and to greater conceptual knowledge. A confirmatory path analysis revealed that these effects can be traced back to the treatment and are not significantly influenced by teacher behavior. Highlights: The use of multiple representations does not automatically lead to better learning outcomes. A basic problem in learning with multiple representations is a possible cognitive overload. Tablet-supported video analysis can reduce extraneous cognitive load in classroom settings. The reduction of extraneous cognitive load leads to a better conceptual understanding. The positive effect is independent of the teacher, which is conducive to dissemination into regular lessons.